Two Conditionalproofs of Riemann Hypothesis - Salah, Jamal Y. Mohammad (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2020)
We consider the analytic continuity of the Riemann zeta function through the Hankel contour. We detect a sort of non accuracy in the functional equation with a significantly small error that we consider to conditionally prove Riemann Hypothesis in two ways.